Different Effects of Quercetin Glycosides and Quercetin on Kidney Mitochondrial Function—Uncoupling, Cytochrome C Reducing and Antioxidant Activity - Kristina Zymone; Raimondas Benetis; Darius Trumbeckas; Ingrida Baseviciene; Sonata Trumbeckaite (Molecules, 2022)
Flavonols are found in plants as aglycones and as glycosides. Antioxidant activity of flavonols may occur via several mechanisms within the cell, and mitochondria as a target may play an important role. There is a lack of information about the influence of the sugar moiety on biological activity of flavonoid glycosides. The aims of study were to investigate the effects of quercetin and its glycosides on mitochondrial respiration rates at various metabolic states, and to evaluate their antioxidant potential using chemical and biological approaches. Mitochondrial function was measured using an oxygraphic method, cytochrome c reduction spectrophotometrically, H2O2 generation in mitochondria fluorimetrically, and antioxidant activity of flavonoids using an HPLC-post column system. Our data revealed that quercetin and its glycosides isoquercitrin, rutin, and hyperoside uncouple kidney mitochondrial respiration (increasing the State 2 respiration rate) and significantly reduce cytochrome c. Moreover, quercetin, and its glycosides decrease the production of mitochondrial H2O2 and possess radical scavenging and ferric reducing capacities. The highest activity was characteristic for quercetin, showing that the sugar moiety significantly diminishes its activity. In conclusion, our results show the efficient radical scavenging, ferric and cytochrome c reducing capacities, and uncoupling properties of quercetin and its glycosides, as well as the importance of the sugar residue and its structure in the regulation of kidney mitochondrial function.